Effect of A Motor Intervention Based on The Guided Discovery Method on The Fundamental Motor Skills of The Child Unit Of 9 Years: Case Study - Morera-Castro, Maria (2019)
The purpose of this research was to determinate the effect of a motor intervention based on the guided discovery method on the fundamental motor skills of a typical child. A 9-year-old child participated in the study, who feels physically active, practices sports regularly, attend primary school and has a normal state of health and cognition. The intervention was applied for 6 weeks, 2 evaluation sessions assess by the IPBM before and after intervention, and 4 practical sessions of 60 minutes, one day of the week for 4 weeks. For the analysis of the results, the percentage of change was used. The results after the intervention showed improvements in the percentage of change in 4 of the locomotor patterns between 33.33% and 300%; in manipulative patterns between 37.5% and 900%; as well as a 50% improvement in total locomotor skills and 85.18% in total manipulative skills. And a global improvement in PBM of 65.08%. Therefore, it is concluded that after this case study, an intervention model based on the method used can be a useful tool to improve fundamental motor skills in children.